2016
DOI: 10.18632/oncotarget.12004
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and imaging biomarkers for hypoxia predict poor outcome in endometrial cancer

Abstract: Hypoxia is frequent in solid tumors and linked to aggressive phenotypes and therapy resistance. We explored expression patterns of the proposed hypoxia marker HIF-1α in endometrial cancer (EC) and investigate whether preoperative functional imaging parameters are associated with tumor hypoxia. Expression of HIF-1α was explored both in the epithelial and the stromal tumor component. We found that low epithelial HIF-1α and high stromal HIF-1α expression were significantly associated with reduced disease specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
(83 reference statements)
1
26
0
Order By: Relevance
“…33 In this study, a low molecular weight contrast agent (Gd-DTPA) was used, which might have some influence on the assessment of the K trans value. Second, HIF-1α expression was observed not only in tumor cells but also in the stromal component of the tumor, 34 but this study observed the HIF-1α expression only in tumor cells, just as in many previous studies. 15,16,20 Therefore, the correlation between multiple imaging parameters and HIF-1α expression in the stromal component of the cervical tumor is unclear and needs to be further investigated.…”
Section: Discussionsupporting
confidence: 55%
“…33 In this study, a low molecular weight contrast agent (Gd-DTPA) was used, which might have some influence on the assessment of the K trans value. Second, HIF-1α expression was observed not only in tumor cells but also in the stromal component of the tumor, 34 but this study observed the HIF-1α expression only in tumor cells, just as in many previous studies. 15,16,20 Therefore, the correlation between multiple imaging parameters and HIF-1α expression in the stromal component of the cervical tumor is unclear and needs to be further investigated.…”
Section: Discussionsupporting
confidence: 55%
“…The 18 F‐FDG PET/CT images were acquired with a Biograph 40 True Point scanner (Siemens, Erlangen, Germany) using an established protocol . 18 F‐FDG was administered by intravenous injection 60–120 minutes before scanning.…”
Section: Methodsmentioning
confidence: 99%
“…In general, hypoxia leads to a reduced response to chemo-and radiotherapy, and we have shown that imaging and tissue markers for hypoxia predict reduced survival in EC [67]. Therefore, detecting hypoxic tumors by preoperative functional imaging might have therapeutic consequences and improve risk-stratification.…”
Section: Oncologic Pet Tracers Relevant For Ecmentioning
confidence: 95%